Propagation of interspecies sexual behaviour between Japanese macaques and Sika deer: First evidence - Sueur Cédric; Oshima Atsuyuki; Pelé Marie (Cultural Science)
This naturalistic note presents a series of observation of interspecies sexual behaviour involving Japanese macaques (Macaca fuscata yakui) and Sika deer (Cervus Nippon yakushimae) on Yakushima Island, Japan. The initial observation in 2015 revealed a male macaque’s attempt to engage in sexual activity with female deer, displaying mate-guarding behaviour. Subsequent observations in 2020, 2021 and 2023 showed the continuation of this behaviour and potentially the propagation to other macaques. We categorised this rare behaviour as a case of reproductive interference and explored hypotheses regarding its functionality. While some suggest nutritional benefits for the deer, others propose learning, incomplete species recognition, or mate deprivation hypotheses. This behaviour may also be selectively neutral, offering no direct fitness benefits, but rather represents a behavioural by-product of other interactions between these two species, which may themselves be adaptive. Furthermore, we hypothesise that the observed propagation may underlie social transmission and highlight the potential cognitive capacities of Japanese macaques involving social learning mechanisms and the willingness to adopt noninstinctual behaviours.